Nano-computed tomography: current and future perspectives - Aly Ahmed, Hany Mohamed (The Korean Academy of Conservative Dentistry, 2016)
The development of novel imaging technologies amplifies the excellence of scientific dental research. Significant technological advances in imaging have been introduced over the years in the field of restorative dentistry and endodontics. X-ray micro-computed tomography (micro-CT) systems were developed in the early 1980s, producing voxels in the range of 5 - 50 μm.1 These micro-CT systems offer a reproducible technique for three-dimensional assessment. Because the imaging process is non-destructive, the same samples can be examined many times and continue to be available after scanning for additional biological and mechanical testing.1,2 In recent years, micro-CT systems have rapidly gained importance as essential components of many academic and industrial research laboratories, and have been used in examining a wide range of specimens including teeth, bone, and materials.1 Newer generations of micro-CT systems also enable in vivo imaging of small live animals.1